CORPORATE INCOME TAX RATES BEFORE AND DURING THE COVID-19 PANDEMIC BASED ON FINANCIAL PERFORMANCE IN (Case Study at PT. Kalbe Farma TBK ) - Tarinih Tarinih; Ghefira Nur Fatimah; Fikry Ramadan Suhendar (Jurnal Ekonomi, 2023)
PT Kalbe Farma Tbk is an Indonesia-based company primarily engaged in the production of health and nutritional and pharmaceutical products. Its business is classified into four segments: prescription drugs, health products, nutritional products and distribution and logistics, During the Covid 19 Pandemic. PT..Kalbe Farma Tbk, one of the companies that is still earning revenue despite a declineThis study aims to determine the calculation of corporate income tax rates before and during the pandemic and to determine the effect of changes in corporate income tax rates on the financial performance of PT Kalbe Farma Tbk. The research method is to use descriptive qualitative methods comparative, this type of research uses case studies. The sample for this research is the financial statements for the 2019 and 2020 periods of PT Kalbe Farma Tbk. The type of data used is secondary data, library data as material for testing and analyzing financial performance before and after the Covid 19 pandemic. The results of the analysis show that the calculation of income tax expense incurred or paid is smaller during the pandemic, namely in 2020, due to changes in tax rates according to with government regulation No 30 of 2020 concerning reducing income tax rates for domestic corporate taxpayers in the form of public companies. In 2019 (before the pandemic) PT Kalbe Farma Tbk was subject to a corporate tax rate of 25%, while in 2020 (during the pandemic) it was subject to a corporate tax rate of 22% and received a 3% reduction to 19%. The results of the study of changes in tax rates on the financial performance of PT Kalbe Farma Tbk in ROA decreased by 0.11% and DER decreased by 2.15%, while ROE increased by 0.13% and NPM increased by 0.9%. in the period after the change in the corporate income tax rate.